O processo de documentação pedagógica em uma experiência formativa na educação infantil: um olhar para a dimensão estética - Lisboa, Anna Carla Luz (2019)
This research aims to theme the pedagogical documentation and its aesthetic dimension from a formative experience of early childhood education teachers. It was carried out in a childhood education institution attached to a university in Tubarão city, south of Santa Catarina state and it has a group of 10 early childhood education teachers as subject. In terms of methodology, the research is guided by a qualitative perspective, it proposes the method as deviation, taking the case studies structure as a way to connect the empirical to the theory. The research methodological direction was created in the way, together, researcher and research subject and it was characterized into a formative experience carried out with teachers during eight meetings from June to November 2018. The meetings purpose was to offer time and an area able to invite them to construct the pedagogical documentation which would narrate their educational practices. Throughout the meetings to document the participative observation, written, photographic and audiovisual records, and above all, be together and with were the research instruments. In the analysis, different authors and perspectives were taken into account as Benjamin (1984), Larrosa (2002, 2016), Malaguzzi (1999, 2016), Rinaldi (2002, 2017), Ostetto (2006, 2010, 2011), Pandini-Simiano (2015), Vecchi (2006, 2017) Hermann (2005), Hoyuelos (2006) e Duarte Jr (1984, 1991, 2000, 2003) among others. As we understand the pedagogical documentation as a peculiar narrative woven during the reunion of adults and children and aesthetic as the concern and attention to the other and his surrounding through connections and sensitivity, the results found were that the documenting act, when asking teachers a more sensitive eye, a respectful listening about the children, raises awareness, yields meanings, expanding possibilities of being and being in the educational context. It was realized how much the aesthetic experience is still necessary to the teachers. Throughout the documenting journey it was possible to identify that teachers, being with of their equals, being listened to and looked at, as well as listening and looking at the other, allowed to strengthen their relationships, to build connections, of their sensibilities, of the aesthetic sense expanding possibilities of being, being and living in company in childhood education.